2010
DOI: 10.1002/cphc.201000363
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Aspects of Electrodeposition for the Realization of Plasmonic Nanostructures

Abstract: Electrodeposition is used for the preparation of nanoparticles and nanostructures that allow, in principle, surface plasmon excitation. The (photo)electrodeposition process of Rh and Au nanoparticles as well as of heterodimeric enzymes onto silicon surfaces is investigated and the resulting structures are discussed with regard to applications in photoelectroctalysis and biosensing. Electrodeposition of Rh onto H-terminated p-Si surfaces generates nanostructures of the metal nanoparticles with simultaneous oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…There are many papers demonstrating that breast cancer oncology may benefit from SERS-active nanoparticles. They have been used in assays for prostate-specific antigen (PSA), BRCA1, and HER2, along with examples of nucleic acid detection. …”
Section: Raman-based Spectroscopy As a Detection Technique For Breast...mentioning
confidence: 99%
“…There are many papers demonstrating that breast cancer oncology may benefit from SERS-active nanoparticles. They have been used in assays for prostate-specific antigen (PSA), BRCA1, and HER2, along with examples of nucleic acid detection. …”
Section: Raman-based Spectroscopy As a Detection Technique For Breast...mentioning
confidence: 99%
“…This drop is distributed according to the thickness and static dielectric constants of the structure according to Fig. 5b [38]. It would lower the band bending to about 0.6 eV.…”
Section: The In Situ Prepared Photovoltaic Devicementioning
confidence: 99%
“…Results using synchrotron radiation photoelectron spectroscopy (SRPES) have shown that the surface of step bunched n‐type Si appears to be in an accumulation condition where the Fermi level at the surface is closer to the conduction band minimum than expected from the doping level 16. For future applications as bio‐sensors, in photoelectrocatalysis and in plasmonic sensing 19 it is of considerable interest to analyze the surface electronic properties, also with regard to their spatial behavior and to correlate them with the surface nanotopography.…”
Section: Introductionmentioning
confidence: 99%